Comparison of Reproductive Health Knowledge and Attitude towards Premarital Sexual Intercourse between Natural Sciences and Social Sciences Students of SMAN 1 Temanggung - Sahir, Endang; Iryawan, Andri; Sahir, Endang (Nexus Kedokteran Komunitas, 2015)
Background: In the globalization of information era, a high number of adolescents with lack of reproductive health knowledge are predicted to cause raising issues of deviant sexual behaviour, HIV/AIDS, and other sexually transmitted diseases. Indonesian government establishes Generation Planning program where reproductive health knowledge is an important aspect that must be examined on a regular basis as part of efforts to build Tough Adolescent. The existence of formal high school education which consists of different scientific fields, naturals and social sciences, becomes the background of this study in order to determine the differences of reproductive health knowledge and attitude towards premarital sexual intercourse between natural sciences and social sciences students of SMAN 1 Temanggung. Methods: This study was an observational analytic study with cross sectional approach. The subjects were students of class XII SMAN 1 Temanggung aged 16-18 years majoring in natural or social sciences in 2014. The sample was 167 students who met inclusion criteria and did not meet exclusion criteria obtained using proportionate stratified random sampling technique. Data taken from the questionnaire were analyzed using Mann-Whitney and Spearman correlation test (Î± = 0.05) by SPSS 16.0 for Windows program. Results: Mann-Whitney test shows significant difference of reproductive health knowledge between natural and social sciences groups (p=0.000, p < 0.05), but the test shows no significant difference of attitudes toward premarital sexual intercourse between two groups (p= 0.128, p> 0.05). Spearman correlation test shows no correlation between the studentâs reproductive health knowledge and their attitude toward premarital sexual intercourse (p value= 0.875, p>0.05). Conclusion: There is significant difference of reproductive health knowledge but there is no significant difference in attitudes toward premarital sexual intercourse between natural and social sciences students of SMAN 1 Temanggung.There is no correlation between the students reproductive health knowledge and their attitudes toward premarital sexual intercourse. Keywords: reproductive health knowledge, attitudes toward premarital sexual intercourse, natural science, social science, Generation Planning.Â